AN OVERVIEW OF WIRELESS SENSOR NETWORK SYSTEM DESIGN USING RASPBERRY-PI FOR REAL TIME ENVIRONMENTAL WATER QUALITY MONITORING AND TREATMENT APPLICATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Drinking water is one of the most important & basic need of human beings. The drinking water is not available in sufficient amount even though 79% of earth's surface is covered with water. One the other hand, the water which is available for the drinking purpose is not of good quality. The need of the time is to develop the monitoring system for the water quality as the water if important for human beings survival. The developing countries like India are continuously supporting the industrial growth. The industrial are growth leads to extra use of water and the waste generated from the water is most of the times disposed in natural water resources. Authors have presented an overview of the water quality monitoring system using Raspberry-pi environment and wireless networks.